A Critical Assessment of Union of the Soviet Socialist Republics and Nigeria Relations during the Period of Nigerian Civil War, 1967-1970 - Ediagbonya Michael (Britain International for Academic Research (BIAR-Publisher), 2022)
The paper examines Nigeria and the Union of Soviet Socialist Republics Relations during the Nigerian Civil War. It discusses the role of USA, Britain and France in the Nigerian Civil war. It analyzes the timely intervention of USSR which supplied military weapons and technical personnel to Nigeria when Britain and USA declined. The researcher obtains data from primary and secondary sources. Oral interviews serve as primary sources. Books, journals, articles, newspapers, projects, theses dissertations were used as secondary sources. It was found that the relationship between Nigeria- USSR in the Pre-civil war period was Lukewarm, non-chalant and sad. It was found that France openly supported the Republic of Biafra while Britain and USA refused Nigeria’s request for weapons to execute the war. It was demonstrated that Nigeria needed weapons to stop the Biafran forces from succeeding and initially relied on Britain and USA to supply the weapons but they were not willing to provide the military assistance. Hence, the federal Government directed their attention to USSR for assistance which the Soviets gradually accepted. In conclusion, it was found that the continuous corporate existence of Nigeria as a sovereign state owns much to the timely assistance provided by USSR during the Nigeria’s trying period.